The size and composition of government debt in the euro area - Dagmar Hartwig Lojsch; Marta Rodríguez-Vives; Michal Slavík (European Central Bank (ECB), 2011)
This paper explains the various concepts of government debt in the euro area with particular emphasis on its size and composition. In terms of size, the paper focuses on different definitions that are in use, in particular the concept of gross general government debt used in the surveillance of the euro area countries, the total liabilities from the government balance sheet approach, and the net debt concept which subtracts government fi nancial assets from the liability side. In addition, it discusses “hidden debt” in the form of implicit and contingent liabilities. In terms of composition, the paper provides information about euro area government debt broken down by maturity, holder or the currency of issue. All these indicators illustrate a sharp increase in government debt in most euro area countries as a result of the crisis. This in turn has several policy implications: (i) the growing government debt ratios need to be stabilised and put on a downward path which improves market confidence; (ii) fiscal surveillance needs to put more emphasis on government debt indicators than in the past; (iii) government financial assets could play a role when analysing solvency issues; (iv) implicit and other off-balance-sheet government liabilities need to be carefully monitored and reported; (v) the gross debt concept should remain the key basis for fiscal surveillance in the EU and for the Excessive Deficit Procedure in particular; (vi) beyond the size of government debt its composition is also a key factor behind public finance vulnerabilities.
Keywords: E31; E58; F41; P24; 330; Fiscal policies; government debt; Stability and Growth Pact.; sustainability; Öffentliche Schulden; Eurozone; Finanzpolitik; Europäischer Stabilitätsmechanismus; EU-Staaten